KEMAMPUAN MENGGAMBAR BEBAS PADA JURNAL PAGI DI TKIT BUNAYYA 7 ALHIJRAH 2 LAUT DENDANG - Sartika Sareany Tambunan (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This research aimed to describe the ability of children to draw freely for group B in TKIT Bunayya 7conducted in the morning jurnal that is 15 minutes before effective learning started. The ability drawing free in this research was skill a child in drawing implement used freely to express the idea,imagination, feelings and expression without compulsion from other people through play of pattern, texture, color, and the object picture. The subject of study 15 chlidrens. Technique data collection used is observation with portofolio. Technique analysis the data used was descriptive analysis quantitative with the percentage. The research results show that the drawing free children in group B including in the predicate good enaugh namely by the percentage 53,7%.